Constructions of the Family in Livy's Ab Urbe Condita - Holbrook, Alexandra L. (My University, 2009)
﻿Livy's Ab Urbe Condita, a history of Rome from its foundations to his own day, has been the subject of much scholarly analysis and criticism. The 35 extant books are primarily a political and military narrative in the tradition of Roman historiography, written at the end of the period known to us as the Republic and in the early decades of Rome's imperial period (ca. 30 BC--14 AD). What is remarkable about the work is the volume of stories and incidental references to family relationships and family life, particularly marriages and parent-child relationships, which often have little bearing on political or military activities. Throughout the AUC, Livy constructs consistent representations of family ideals according to the features of traditional morality that were dominant during his own day, applying them even to periods in which Roman society was likely quite different. His stories include emphatic and vivid exempla of traditionally appropriate behaviour between husbands and wives and in sexual behaviour as well as reciprocal duties between parents and their children. The explanations for Livy's keen interest in family relationships lie both in his own background and in the socio-political turbulence of the period during which he matured and began to write his history. During this same period, Augustus rose to political prominence and invoked a similar set of moral values in his programme of cultural renewal, in legislation as well as visual culture. The elements of this programme can be usefully compared to Livy's constructions of family ideology to further inform and articulate the scope of moral concerns which were of interest to politically and culturally active Romans of the first century BC.
Keywords: Livy's Ab Urbe Condita, Rome, family, relationships, traditional, morality